Gagasan Muhammad Arkoun Tentang Humanisasi Ilmu Agama dan Relevansinya Bagi Pengembangan Ilmu Falak - Alpaten, Ulil Albab Al aulia; Putra, Nur Afdal Purnama; Khairunnisa, Ariba; Qolbi, Yusuf Nur; Aulia, Rizka (DIKTUM: Jurnal Syariah dan Hukum, 2024)
Muhammad Arkoun, as one of the contemporary Islamic thinkers, is the subject of examination in this writing, where the author seeks to explore Arkoun's ideas on the humanization of religious knowledge and its relevance to the development of astronomy in the present era. To achieve this objective, the author employs the library research method, which is literature-based. Arkoun's notions of deconstruction and rethinking Islam constitute key concepts presented in his critique of Islamic societies that tend to sanctify the views of past scholars without considering their relevance to the current context. According to Arkoun, this tendency often results in Islamic thought becoming stagnant, hindering the ability to address contemporary issues due to a fixation on the perspectives of earlier scholars. This problem extends to the realm of knowledge development, as seen in cases such as the rejection of reorienting the qibla direction in certain mosques. The argument is based on the belief that the qibla direction in these mosques is a legacy from past scholars of the region and, therefore, should not be altered. However, Arkoun contends that, in the field of astronomy, calculations reveal that the qibla direction in these mosques deviates, necessitating a correction in their positioning.